Employee Satisfaction and Customer Delight-insights from Indian Hospitality Industry - Singh, Jaideep (International Journal of Psychosocial Rehabilitation, 2020)
Hospitality Sector in India is one of the largest sectors in terms of contribution to GDP. Over last few years the growth in hospitality sector has witnessed increasing importance of customer delight, service profit chain, its component constructs and linkages between the employee job satisfaction and customer delight. The study aims to provide a comprehensive review on the linkages between the employee job satisfaction and customer delight. A broader attitude unveils the point that the employees in an organization are entangled together to perform better and even better with each adding day of their experience, which in turn will not only generate revenue for the organization, but will also result into utmost customer satisfaction. Furthermore, the consequences like customer satisfaction was dealt deeply, studies revealed that both customer satisfaction and loyalty are meaningfully related to the employee’s outlook at the job. Thus, a satisfied, motivated and happy employee was marked allegedly with the customer satisfaction, quality work, and profitability to the organization. The focus of the study is to understand the effects of satisfaction of employees on Customer Delight, this study in turn will be highly useful for the hospitality sector in the long run. The results of the study provide an insight to the relationship of customer delight with employee satisfaction which will be of great use to the industry and will invite future scope for research.